Current Animal Models of Postoperative Spine Infection and Potential Future Advances - Stavrakis, A. I.; Loftin, A. H.; Lord, E. L.; Hu, Y.; Manegold, J. E.; Dworsky, E. M.; Scaduto, A. A.; Bernthal, N. M. (Frontiers in Medicine, 2015)
Implant related infection following spine surgery is a devastating complication for patients and can potentially lead to significant neurological compromise, disability, morbidity, and even mortality. This paper provides an overview of the existing animal models of postoperative spine infection and highlights the strengths and weaknesses of each model. In addition there is discussion regarding potential modifications to these animal models to better evaluate preventative and treatment strategies for this challenging complication. Current models are effective in simulating surgical procedures but fail to evaluate infection longitudinally using multiple techniques. Potential future modifications to these models include using advanced imaging technologies to evaluate infection, use of bioluminescent bacterial species, and testing of novel treatment strategies against multiple bacterial strains. There is potential to establish a postoperative spine infection model using smaller animals, such as mice, as these would be a more cost-effective screening tool for potential therapeutic interventions.